E-guidelines for the effectiveness of E-government process - (:unkn) unknown (IGI Global, 2015)
Computers, the Internet, smart phone technology and other innovations have come about through the developments in technology which have helped to increase the type and number of facilities available to mankind. E-government applications have led the way in the development of these facilities. Today, transactions that used to take a great deal of time can be done in hours, even minutes, with the aid of e-government applications. In e-government processes it is essential that citizens, especially those who are of a certain age and not very familiar with the Internet, can carry out the relevant e-government applications with ease. At this point, e-guidelines that explain the e-government process and applications take on a strategic importance. In this chapter, e-guidelines in the e-government process will be examined; to date, this topic has not been examined in many studies. By emphasizing the importance of developing e-guidelines, the characteristics, usage areas and importance of e-guidelines will be examined and an example e-guideline for the Turkish e-government process, which provides 562 different services from 70 different institutions, will be examined. © 2015, IGI Global.